AKUT PANKREATİT TANISIYLA TAKİP EDİLEN ÇOCUKLARIN RETROSPEKTİF İNCELEMESİ - ÜNSAL, SAVAŞ KAAN (Fırat Üniveristesi, 2022)
Akut pankreatit, farkındalığın ve laboratuvar ve radyolojik incelemelerin artmasıyla birlikte son yıllarda çocukluk çağında sıklığı artmakta olan inflamatuar bir hastalıktır. Yaptığımız çalışmada akut pankreatit tanısı alan çocuklarda demografik, etyolojik, klinik, laboratuvar, radyolojik bulgularının, hastalığın prognozunun değerlendirilmesi amaçlanmıştır. Hastanemizde Ocak 2010- Nisan 2021 tarihleri arasında Çocuk Sağlığı ve Hastalıkları servisine yatırılarak akut pankreatit tanısı konulmuş ve takiplerde akut rekürren ve kronik pankreatit tanısı almış toplamda 108 çocuk hasta incelendi. International Study Group of Pediatric Pancreatitis: In search for a cure (INSPPIRE) tarafından belirlenmiş olan 3 kriterden en az 2 kriteri sağlayan hastalarda akut pankreatit tanısı konuldu ve çalışmaya dahil edildi. Akut pankreatit tanısı almış olan 108 hastanın 54'ünü erkek, 54'ünü kız cinsiyet oluşturdu. Hastaların başlangıç yaşı 2-17 yaş, yaş ortalaması 9,96 ± 4,8 olarak raporlandı. Hastalarda etyolojisi idiyopatik olanlar %19,4 oranında ve sebebi belirli olanlarda hiperlipidemi %19,4 oranında görüldü. Hastalarda en sık başvuru şikayeti kusmaydı (%60,2). Laboratuvarda amilaz ve/veya lipaz düzeylerinde 3 kat ve üzeri artış olması tanı kriteriydi. Diğer laboratuvar parametrelerinde serum reaktif protein (CRP) düzeylerindeki artış anlamlı olarak değerlendirildi. Hastalarda yapılan radyoloji incelemelerde %94,4 hastada ultrasonografi, %38 hastada bilgisayarlı tomografi, %71,3 hastada magnetik rezonans kolanjiopankreatografi sonuçları pankreatit ile uyumlu olarak raporlandı. Akut pankreatit laboratuvar ve radyolojik görüntüleme imkanlarının artmasına rağmen çocukluk çağında önemli bir inflamatuar hastalık olmaya devam etmektedir. Hastalara mayi desteği ve destek tedavisi tedavide en önemli yaklaşımı oluşturmaktadır. Hastalığın erken tanı ve tedavisiyle hastalığa bağlı morbidite ve mortalite önlenebilmektedir.

Acute pancreatitis is an inflammatory disease that has been increasing in frequency in childhood in recent years with the increase in awareness and laboratory and radiological examinations. In our study, it was aimed to evaluate the demographic, etiological, clinical, laboratory and radiological findings and prognosis of the disease in children diagnosed with acute pancreatitis. A total of 108 pediatric patients who were admitted to the Pediatrics Department of our hospital between January 2010 and April 2021 and diagnosed with acute pancreatitis and diagnosed with acute recurrent and chronic pancreatitis during follow-up were examined. A diagnosis of acute pancreatitis was made in patients who met at least 2 of the 3 criteria determined by the International Study Group of Pediatric Pancreatitis: In search for a cure (INSPPIRE) and were included in the study. Of the 108 patients diagnosed with acute pancreatitis, 54 were male and 54 were female. The age of onset of the patients was reported as 2-17 years, with a mean age of 9.96 ± 4.8 years. The rate of patients with idiopathic etiology was 19.4% and the rate of hyperlipidemia was 19.4% in patients with specific etiology. The most common complaint in patients was vomiting (60.2%). A 3-fold or more increase in amylase and/or lipase levels in the laboratory was the diagnostic criterion. The increase in serum reactive protein (CRP) levels in other laboratory parameters was evaluated as significant. In the radiological examinations of the patients, ultrasonography in 94.4%, computed tomography in 38%, and magnetic resonance cholangio pancreatography in 71.3% of patients were reported to be consistent with pancreatitis. Acute pancreatitis continues to be an important inflammatory disease in childhood despite the increase in laboratory and radiological imaging opportunities. Fluid support and supportive treatment constitute the most important approach in treatment. Disease-related morbidity and mortality can be prevented by early diagnosis and treatment of the disease.
Retrospective examination of children following WİTH A diagnosis of acute pancratitis
Keywords: Çocuk Sağlığı ve Hastalıkları